2017
DOI: 10.2147/bctt.s111394
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on CHEK2 mutations in breast cancer

Abstract: Checkpoint kinase 2 (CHEK2) is a serine/threonine kinase which is activated upon DNA damage and is implicated in pathways that govern DNA repair, cell cycle arrest or apoptosis in response to the initial damage. Loss of kinase function has been correlated with different types of cancer, mainly breast cancer. CHEK2 functionality is affected by different missense or deleterious mutations. CHEK2*1100delC and I157T are most studied in populations all over the world. Although these variants have been identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 42 publications
3
91
0
Order By: Relevance
“…Similarly, we found that in BRCA samples ( Fig. 2e), for the prediction of expression levels for genes involved in cell-cycle regulation (Cell Cycle: G2/M DNA Damage Checkpoint Regulation, Cell cycle control of chromosomal Replication, Mitotic Roles of Polo-Like Kinase), but also for the prediction of expression levels for CHEK2 (a gene known to be mutated in breast cancer 40 and involved in its progression 41 ) and Cyclin E (known to be overexpressed in breast cancer 42 ). These results demonstrate that HE2RNA, despite training on a diverse range of cancer types, was able not only to predict expression levels for genes involved in immune regulation, but also to detect pathways deregulated in specific types of cancer.…”
supporting
confidence: 58%
“…Similarly, we found that in BRCA samples ( Fig. 2e), for the prediction of expression levels for genes involved in cell-cycle regulation (Cell Cycle: G2/M DNA Damage Checkpoint Regulation, Cell cycle control of chromosomal Replication, Mitotic Roles of Polo-Like Kinase), but also for the prediction of expression levels for CHEK2 (a gene known to be mutated in breast cancer 40 and involved in its progression 41 ) and Cyclin E (known to be overexpressed in breast cancer 42 ). These results demonstrate that HE2RNA, despite training on a diverse range of cancer types, was able not only to predict expression levels for genes involved in immune regulation, but also to detect pathways deregulated in specific types of cancer.…”
supporting
confidence: 58%
“…The interpretation of this challenge is problematic since the exact nature of the association between CHEK2 and breast cancer is debatable (Apostolou & Papasotiriou, ). Moreover, the frequency of the variants is too low to make pathogenicity annotations: Twenty‐four variants were seen once (either in a case or in a control), six variants two times, two variants three times, one variant four times, and one variant 17 times.…”
Section: Resultsmentioning
confidence: 99%
“…The interpretation of this challenge is problematic since the exact nature of the association between CHEK2 and breast cancer is debatable (Apostolou & Papasotiriou, 2017). Moreover, the frequency of the variants is too low to make pathogenicity annotations:…”
Section: Other Considerationsmentioning
confidence: 99%
“…Checkpoint kinase 2 ( CHEK2 ) has been demonstrated to be an effector kinase in the DNA damage checkpoint pathway, thus variations in its sequence can lead to detrimental outcomes in downstream DNA replication processes (Chaturvedi et al, ). CHEK2 alterations by single nucleotide variants (SNVs) are linked to DNA damage that is implicated in cases of breast cancer (BC; Apostolou & Papasotiriou, ). BC is the most commonly diagnosed cancer among female Hispanics in the United States and the leading cause of cancer related deaths (Lynce et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…CHEK2 alterations by single nucleotide variants (SNVs) are linked to DNA damage that is implicated in cases of breast cancer (BC; Apostolou & Papasotiriou, 2017). BC is the most commonly diagnosed cancer among female Hispanics in the United States and the leading cause of cancer related deaths (Lynce et al, 2016).…”
Section: Introductionmentioning
confidence: 99%